1964
DOI: 10.1139/m64-055
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Varied Temperature on the Kinetics of Metabolism of Gibberella Fujikuroi in Stirred Culture

Abstract: The metabolism of Gibberclla Jujikuroi in stirred culture has been studied at varied temperatures over the range 8–40 °C. Two nitrogen-limited media were used, which differed only in the initial concentration of ammonium tartrate. Economic and rate constants have been derived at each stage of fermentation, and methods of relating these to temperature discussed. Each has been related to temperature both by a linear plot, and according to the Van"t Hoff – Arrhenius model.There was no significant difference betwe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
4
0

Year Published

1965
1965
2020
2020

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 23 publications
(6 citation statements)
references
References 8 publications
2
4
0
Order By: Relevance
“…Similar profile was reported for GA 3 production in Pseudomonas wherein a maximum yield of 0.3 g/L was obtained at pH 7.0 [6]. However, Borrow et al [11] reported that GA 3 production decreases when the pH was outside the range of 3.0-5.5 in a stirred culture. The growth of the fungi was however better at pH 8.0 (data not shown).…”
Section: Optimization Of Ph In Submerged Fermentationsupporting
confidence: 78%
“…Similar profile was reported for GA 3 production in Pseudomonas wherein a maximum yield of 0.3 g/L was obtained at pH 7.0 [6]. However, Borrow et al [11] reported that GA 3 production decreases when the pH was outside the range of 3.0-5.5 in a stirred culture. The growth of the fungi was however better at pH 8.0 (data not shown).…”
Section: Optimization Of Ph In Submerged Fermentationsupporting
confidence: 78%
“…For purposes of clarity, these tracings, or curves transposed from them, will be referred to as temperature-growth profiles. The profiles resemble the Arrhenius plot presented by Ingraham (1958) and the more recent temperature relationships reported by Borrow et al (1964); undoubtedly they are a measure of the same general reaction of biological systems to temperature, although in the present instance the ordinate is not rate, but relative turbidity.…”
Section: Resultssupporting
confidence: 77%
“…The effect of lowering the pH is to decrease the rate of growth but not, the concentration of lipid produced-the latter, in fact, may be increased. Raising the temperature can be expected to improve growth up to an optimum at c. 30" and possibly a maximum np to 36" with little change in metabolism (Borrow et al, 1964). Temperatures up to 35" were successfully used by Enebo & Iwamoto (1966), and it is possible that at this temperature and in conjunction with a pH as low as 2.5 (at which R. gracilis can grow) more significant changes in the composition of the fatty acids may be produced.…”
Section: General Conclusionmentioning
confidence: 99%